Old Money, the Nouveaux Riches and Brunhilde's Marriage Strategy - Anne-Kathrin Bronsert; Amihai Glazer; Kai A. Konrad (Institute for the Study of Labor (IZA), 2014)
A woman assessing the wealth of a potential husband may observe some, but not all, of his wealth. She may screen, leading to status consumption and wasteful gift giving. The screening activity is costly not only for the potential husband, but also for the woman, as it reduces the wealth of the man she may marry. A sound observable financial background ('old money') benefits the candidate but also the woman, and reduces wasteful status consumption spending. Also, aging and attractiveness of the woman affect the equilibrium conspicuous spending pattern.
Keywords: J12; D82; 330; marriage; screening; search; conspicuous consumption; status